Maintaining, relinquishing, and adapting bonds in bereavement: A qualitative study of grave sweeping in China - Becky Yang Hsu; Roman Palitsky (Elsevier, 2023)
Background: Continuing bonds with the deceased are essential and ongoing aspects of bereavement. In China, the annual ritual of grave sweeping involves family members visiting the graves of their loved ones to offer items and conversation. However, the connections between the specific practices and bereavement have not been thoroughly investigated. Purpose: This article explores how continuing bonds may be maintained through the ritual of grave sweeping, which is part of the communal religion that is practiced by a majority of the population in China. Methods: Utilizing a multiple case study design, we examine the ritual activities of grave sweeping with four ethnographic observations and two in-depth interviews conducted in 2014-2015 in western, southern, and northern regions of China (Sichuan, Xiamen, Harbin, and Qiqihar). Our analysis focuses on qualitative data collected on objects, affect, language, and interactions between participants to better understand the activities involved in the ritual. Results: The acts of offering food, gifts, and engaging in conversation with the deceased during the ritual of grave sweeping provide family members with opportunities to maintain and transform their relationship with the deceased. This practice involves a combination of familiar gestures, such as offering food, as well as differences in the way they interact, such as the food being not consumed together. The actions establish an experience of social exchange between family members and their deceased loved one. Conclusions: Grave sweeping provides an interactional setting for survivors to maintain, relinquish, and adapt bonds to the deceased. Other ritual practices in different settings may offer similar opportunities for continuing bonds.